Consumer perception, preferences and behavioural intention towards choice of certified sustainable palm oil in the Klang Valley, Malaysia - Dauda, Suleiman Alhaji (2021)
Expansion in the commercial oil palm over the last few decades, because of increase in the global demand for palm oil, has given impetus to rapid infrastructural transformation and socio-economic development in Malaysia. However, despite the importance of palm oil, it was alleged to have negative impact on the environment especially natural forest, through loss of biodiversity, emission of greenhouse gas, displacement of indigenous people etc. The aim of the study is to examine the consumer choice of certified sustainable palm oil. The study objective investigates the consumer perception, determine their preference for sustainable palm oil with environmental attributes and appraise the consumers’ behavioural intention toward the choice of sustainable palm oil. A self-administered interview via structured questionnaire of choice experiment and structural equation model was administered to 322 consumers in Klang Valley Malaysia. Information on the consumer perception of palm oil, based on its importance, contribution to the economy, and effect on the environment was analysed. The result on the consumer perception information indicates that, knowledge, awareness, and positive opinion of the consumers to support sustainable palm oil in Malaysia is high. Choice experiment was analyzed using Conditional Logit and Mixed Logit Models. Estimate of consumers’ willingness to pay price premium for palm oil with sustainability attributes was obtained, and heterogeneity in consumer preferences was revealed. Results of choice experiment models indicates consumer preference for Mass Balance supply chain model, moderate levels biodiversity conservation and carbon dioxide emission. Education, income, and gender were the main interaction variables that influences consumer choice for the attributes in the models. Conditional logit model result with interaction indicates mean willingness to pay price premium above the stock price for palm oil produced through Mass Balance process at 5.17% while Segregation through process was 1.95%. price premium for Moderate conservation of biodiversity was 3.85% and for moderate emission of carbon dioxide was 0.86%, while high biodiversity conservation and lower emission was 1.71% and 1.34% respectively. In another vein, result for interaction Mixed logit model has mean willingness to pay price premium above the stock price for palm oil produced through Mass Balance process at 5.10% while Segregation through process was 2.02%. price premium for Moderate conservation of biodiversity was 3.88% and for moderate emission of carbon dioxide was 1.77%, while high biodiversity conservation and lower emission was 1.68% and 1.35% respectively. Structural equation model was also analysed based on protection motivation theory to appraise the consumers’ behavioural intention for their need to protect self or their environment from the effect of unsustainable oil palm expansion. Findings from the structural equation model indicate, consumers negative threat appraisal and positive coping appraisal on one hand, extension of same model to include Roundtable on Sustainable Palm Oil constructs, the result indicated that consumers felt threatened without the intervention of the sustainable certification of palm oil. However, they perceived strategies adopted for addressing the problems associated with oil palm such as loss of biodiversity and emission of harmful carbon dioxide as inadequate and needs improvement. The outcome of this study indicates consumer willingness to promote and protect the environment through their choice of sustainable palm oil. Finding from this study will guide policy makers to incorporate consumers’ demandside when setting sustainable palm oil standard. the study recommended that, to promote environmental sustainability vis a vis expansion of oil palm, there is need stimulate consumer support and also put in place enabling institutional mechanism that will balance the trade-off between oil palm (Economy) and environmental attributes (Ecology).